Gender Disparity in the Safety and Efficacy of Radial and Femoral Access for Coronary Intervention: A Systematic Review and Meta-Analysis. (October 2016) - Huang, Fang-Yang; Huang, Bao-Tao; Wang, Peng-Ju; Zhang, Chen; Zuo, Zhi-Liang; Liao, Yan-Biao; Xia, Tian-Li; Gui, Yi-Yue; Peng, Yong; Liu, Wei; Chen, Mao; Zhu, Ye
Our aim was to investigate the gender disparity in the safety and efficacy of transradial percutaneous coronary intervention (PCI; TRI) and transfemoral PCI (TFI) by a meta-analysis. MEDLINE, Embase, and CENTRAL were searched to identify studies on vascular access with sex-specific events available or studies on sex difference with the events reported by vascular access. Fifteen studies involving 3 921 848 participants were included. Transradial PCI significantly reduced the risk of bleeding complications in both sexes (TRI-versus-TFI odds ratio [OR]: 0.37 in females vs 0.47 in males) and major adverse cardiac events (MACE) in females (OR: 0.70, P < .001) but not in males (OR: 0.83, P = .15) compared to TFI. Transradial PCI diminished the sex difference in the incidence of bleeding complications (female-versus-male OR: 1.82 with TRI vs 2.39 with TFI; interaction P = .01) and MACE (female-versus-male OR: 1.21 with TRI vs 1.41 with TFI; interaction P = .003) compared to TFI. Females were associated with higher crossover rate in the TRI subgroup but not in the TFI subgroup (interaction P = .05). In conclusion, TRI may improve the safety and efficacy of outcomes in both sexes and be an effective means to cut down the gender difference in prognosis.